Effects of testicular sperm aspiration upon first cycle ICSI-ET for type 2 diabetic male patients. (1st November 2020) - Liu, Xiang; Gao, Ming; Sun, Jianhua; Sun, Zheng; Song, Juan; Xue, Xia; Zhang, Zhou; Shi, Juanzi; Xing, Junping
ABSTRACT: Male diabetes mellitus (DM) can affect erectile function and sperm quality. In severe cases, DM can lead to retrograde or no ejaculation, so testicular sperm aspiration (TESA) is combined with intracytoplasmic sperm injection (ICSI) to treat subfertility and infertility for DM couples. However, the effect of TESA upon ICSI (TESA-ICSI) for DM patients remains unclear. This research investigated the effect of TESA-ICSI on first cycle ICSI-embryo transfer (ICSI-ET) for type 2 diabetic mellitus (T2DM) patients and the potential mechanisms. The subjects consisted of 1219 male patients with azoospermia or retrograde ejaculation who were treated with TESA-ICSI from 2015.01 to 2019.11. They were classified into two groups, the T2DM group (n = 54) and non-diabetic control group (n = 1165). Sperm selection for injection was performed using motile sperm organelle morphology examination criteria. The number of available embryos and the high-quality embryo rates following a single ET as well as cleavage, fertilization, implantation, clinical pregnancy and the abortion rates were noted. Compared with the non-diabetic group, the available embryo rate (75.20 ± 26.40% vs.78.36 ± 23.25%) and high-quality embryo rate (46.49 ± 30.37% vs. 47.55 ± 28.57%) in the T2DM group were lower and the abortion rate (20.83% vs. 8.88%) was higher, but these differences were not statistically significant. There were no significant differences in clinical pregnancy, implantation, normal fertilization, and cleavage rates between the two groups. The results show that TESA for male T2DM patients does not influence the effect of ICSI. For T2DM patients with severe oligozoospermia, asthenospermia, teratozoospermia, or retrograde ejaculation that do not meet ICSI criteria, TESA-ICSI may perhaps be considered for reproductive assistance. Abbreviations: DM: diabetes mellitus; TESA: testicular sperm aspiration; ICSI: intracytoplasmic sperm injection; ICSI-ET; ICSI-embryo transfer; LH: luteinizing hormone; mL: milliliter; TES: testosterone; FSH: follicle-stimulating hormone; P: progesterone; HCG: human chorionic gonadotropin